DAMPAK KENAIKAN TARIF OJEK ONLINE TERHADAP PENDAPATAN PENGEMUDI DAN KEPUASAN PENUMPANG, TINJAUAN SEBELUM PANDEMI COVID 19 - Risdiyanto, Risdiyanto; Kurniawan, Tanjung; Alfed, Johary (JURNAL TEKNIK SIPIL, 2021)
Tariff and service are two important elements in online transportation. With the increase in rates, it will affect the income of drivers and passenger services. The purpose of this study is to determine the impact of the increase in online motorcycle taxi rates in 2019 when compared to 2018. Research in 2019 is a continuation of research in 2018. Data was obtained by conducting interviews with 200 passengers and 100 online motorcycle taxi drivers (Gojek) for each year. The impact of the tariff increase on driver's income is carried out by comparing the amount of income between 2019 and 2018. The Customer Satisfaction Index method was chosen to determine the service performance of online motorcycle taxis. Based on the analysis, the results show that the driver's income in the 2019 study has increased compared to 2018. In terms of service, the CSI value has increased. This shows that after the tariff increase, online motorcycle taxi transportation services are getting better